Implementasi Hukum Militer dalam Penegakan Disiplin Anggota TNI di Wilayah Perbatasan - Irwan Triadi; Aprilian Nurahsan Ismail (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
The application of military law in areas of high security risk presents complex challenges for field commanders. In conditions that are often unstable, such as in border areas or conflict zones, commanders must maintain troop discipline while ensuring the effective implementation of operational tasks. Taking into account the problems in this research, the research method used is a normative legal research method. Normative legal research is an activity that cites aspects originating from positive law. Normative legal research originates from applicable statutory provisions, Jurisprudence or Court Decisions, Legal Theory and Doctrine. This research was mostly carried out on secondary data in libraries. The main challenges faced include the stressed physical and mental condition of soldiers, limited resources, and persistent security threats. Field commanders need to apply military law strictly, but must also be wise in understanding the situations their soldiers face in the field. Additionally, they must make quick and sound decisions under pressure, often without adequate logistical or communications support from central command. Commanders must also consider the geopolitical impact of military actions in border areas, where any breach of discipline could affect the stability of local security as well as diplomatic relations. Therefore, adaptive leadership capabilities, deep contextual understanding, and good risk management are the keys to success in implementing military law in areas with high security risks.